2016
DOI: 10.1021/acsnano.6b02712
|View full text |Cite
|
Sign up to set email alerts
|

A Wulff in a Cage: The Confinement of Substrate-Based Structures in Plasmonic Nanoshells, Nanocages, and Nanoframes Using Galvanic Replacement

Abstract: Galvanic replacement reactions carried out on solid core-shell structures typically yield a noble metal nanorattle geometry in which a mobile core is contained within a hollowed shell. Here, we adapt this colloidal synthesis to substrate-based structures to obtain a fundamentally altered product in which an immobilized core is separated from the shell by a well-defined gap, an architecture unobtainable using colloidal techniques and that offers unique advantages in terms of generating plasmonic near-field effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 59 publications
1
52
1
Order By: Relevance
“…The XRD data, when correlated with the observed faceting relative to the substrate alignment flat, indicates that the cuboctahedrons have two orientational relationships with the substrate that are given by (111)[–211] Cu ∥(0001)[11–20] sapphire and (111)[21–1–] Cu ∥(0001)[11–20] sapphire . These relationships are in agreement with those observed for Au[23a] and Pd nanostructures on sapphire. Neither the spherical seeds nor the cuboctahedron templates show any peaks corresponding to Cu 2 O or CuO.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The XRD data, when correlated with the observed faceting relative to the substrate alignment flat, indicates that the cuboctahedrons have two orientational relationships with the substrate that are given by (111)[–211] Cu ∥(0001)[11–20] sapphire and (111)[21–1–] Cu ∥(0001)[11–20] sapphire . These relationships are in agreement with those observed for Au[23a] and Pd nanostructures on sapphire. Neither the spherical seeds nor the cuboctahedron templates show any peaks corresponding to Cu 2 O or CuO.…”
Section: Resultssupporting
confidence: 91%
“…The oxidation of Cu nanostructures has been well‐documented by monitoring its deleterious influence upon the plasmon resonance,[19f,20a,22] which over an extended period of time sees the plasmon peak extinguished. In previous studies, we have demonstrated the galvanic replacement of substrate‐supported templates formed in the vapor phase . Here, we demonstrate a related synthetic scheme for the formation of highly faceted substrate‐supported Cu templates and their subsequent transformation into the CuRh shells using aqueous galvanic replacement reactions.…”
Section: Introductionmentioning
confidence: 78%
“…The length of nanothorns can be easily tailored by controlling the amount of ethanolamine in the reaction system. Similar to hollow structures with intact surface, these open structures could also be utilized as containers to incorporate core materials . For example, Neretina and co‐workers reported the synthesis of Wulff‐shaped nanostructures confined within nanoframes through solution‐based growth modes on substrate‐based templates .…”
Section: Overview Of the Evolution Of Hollow Structuresmentioning
confidence: 99%
“…Similar to hollow structures with intact surface, these open structures could also be utilized as containers to incorporate core materials . For example, Neretina and co‐workers reported the synthesis of Wulff‐shaped nanostructures confined within nanoframes through solution‐based growth modes on substrate‐based templates . As presented in SEM images, Wulff‐shaped Pt nanoparticle can be incorporated into a Wulff‐shaped or cube‐shaped Ag nanoframe after a sequential coating and selective etching process (Figure k,l).…”
Section: Overview Of the Evolution Of Hollow Structuresmentioning
confidence: 99%
See 1 more Smart Citation